Revisiting land reforms in developing countries with a focus on Sub-Saharan Africa - Ghebru, Hosaena (International Food Policy Research Institute, 2021)
The impact of land tenure systems in developing countries on agricultural investment and productivity continues to be the subject of intense scrutiny. This paper looks at land reforms with emphasis on lessons from Africa south of the Sahara (SSA). Food security crises in developing countries in the past decades have revived the debate about whether land tenure systems constrain farmer innovation and investment in agriculture. Changes in tenure systems can potentially have major implications for agricultural transformation. This chapter summarizes the arguments about how best to provide land tenure security in SSA and reviews recent experience and evidence arising from innovative interventions, with implications for other developing regions as well. It is hoped that the experiences and topics analyzed here may also help Venezuela in the process of normalizing land tenure systems in that country.